Future bean demand - Schiek, Benjamin E.; Bonilla Cedrez, Camila; Prager, Steven D. (Bioversity International and the International Center for Tropical Agriculture, 2021)
Bean demand is projected to rise sharply throughout the developing world, in tandem with rising populations, both in absolute terms and relative to other staple crops. The surge will be especially pronounced in Sub-Saharan Africa, where population is projected to surpass 2.5 billion by 2050.